Daughters of the new year : a novel - Tran, E. M. (Elizabeth M.) (Hanover Square Press, 2022)
In New Orleans, three daughters of a former beauty queen and Vietnamese refugee obsessed with zodiac signs are trying to go about their modern lives, but begin to encounter strange glimpses of long-buried secrets from their ancestors.